1970
DOI: 10.3126/nelta.v15i1-2.4612
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Writing in EFL/ESL Context: Balancing Product and Process in Writing Class at Tertiary Level

Abstract: This article presents the findings of an interventionist study designed to examine the effects of productKey words: Teaching English writing, the process approach, the product approach, incorporation of product process approach, guided brainstorming, top down approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 17 publications
2
59
0
6
Order By: Relevance
“…The current practice in schools which focuses on copying sample essay seems to take over all the stages involved in the approach. As a result, the students fail to assimilate critical thinking into their creative writing when they tend to memorize and replicate a model (Hasan & Akhand, 2010). This attitude can lead to plagiarist tendencies among learners.…”
Section: Merit and Demerits Of Product Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The current practice in schools which focuses on copying sample essay seems to take over all the stages involved in the approach. As a result, the students fail to assimilate critical thinking into their creative writing when they tend to memorize and replicate a model (Hasan & Akhand, 2010). This attitude can lead to plagiarist tendencies among learners.…”
Section: Merit and Demerits Of Product Approachmentioning
confidence: 99%
“…Literature has indicated that product approach stresses on the content of the text as well as the score obtained (Hasan and Akhand, 2010). In this approach, students are required to finish texts in terms of language accuracy.…”
Section: Product Approach In Teaching Writingmentioning
confidence: 99%
“…This approach is considered as an extension of the product-oriented approach because students have to study a wide variety of writing patterns (Tangpermpoon, 2008). However, Hasan and Akhand (2010) say that this approach pays less attention to the learner's expression which is a disadvantage to achieve creativity and critical thinking.…”
Section: Genre Based Approachmentioning
confidence: 99%
“…Basnet's (2008) study on proficiency of the students in guided writing found that the guided writing proficiency of the PCL first year students of faculties of humanities and social sciences i.e., 62.08% was found better than that of the students of faculties of education i.e., 60.87%. Hasan and Akhand (2010) wrote an article on approaches to writing in ESL/EFL context: Balancing product and process in writing class at tertiary level which aimed to examine the effects of product and process approach to writing on learners' performance and found the advantages of using a productprocess approach to gauging the effects of writing tasks were appraised. Similarly, Acharya's (2010) research on "Activities used in teaching essays concluded that the teachers did not motivate as it is required, large percentage of teacher (70%) translated difficult words into mother-tongue.…”
Section: Review Of Related Literaturementioning
confidence: 99%